Quantifying antimicrobial use and trends in commercial poultry and dairy farms in Bangladesh - Mohammad Eliyas; Kazi Tahmina Karim; Muzaffar Goni Osmani; Sk Shaheenur Islam; Easrat Jahan Esha; Nure Alam Siddiky; Kazi Kamaruddin; Nelima Ibrahim (PLoS ONE, 2026)
Antimicrobial resistance (AMR) continues to be detected in bacteria from food producing animals in Bangladesh. Globally, as well as in many low- and middle-income countries (LMICs), antimicrobial use (AMU) is identified as the primary driver of rising AMR. This pilot study aimed to quantify AMU in poultry (broiler and layer) and dairy farms in Gazipur and Chattogram districts, assessing seasonal and species-specific AMU patterns. A longitudinal survey conducted during the summer and winter seasons of 2022–2023 involved 36 purposively selected farms (12 each broiler, 12 layer and 12 dairy). AMU was quantified using kilograms of antimicrobial active ingredients (AAIs) and milligrams per population correction unit (mg/PCU). AMU quantity was highest in layer farms (285.80 mg/PCU), followed by broilers (173.29 mg/PCU) and dairy farms (3.56 mg/PCU). Seasonal variations revealed lower AMU levels in broilers (125.68 mg/PCU) and layers (130.48 mg/PCU) in winter, whereas dairy usage increased in winter (13.93 mg/PCU). Predominantly used AAI’s included neomycin (broilers, both seasons), oxytetracycline (layers in summer), tylvalosin (layers in winter), sulfonamides (dairy in summer), and penicillin (dairy in winter). Poultry farms utilised substantially higher AMU quantities. Notable geographic differences in AMU quantities used in broiler and layer farms were observed, while dairy farms showed uniform use across districts. Of important public health concern is the high proportion (65–90%) of antimicrobials that fall under the World Health Organization’s (WHO) Medically Important Antimicrobial (MIA) categories, particularly Critically Important (CIA) or Highest Priority Critically Important Antimicrobials (HP-CIA), as well as the substantial use of Watch- and Reserve-group antimicrobials according to the WHO AWaRe framework. These findings highlight excessive use of medically important antimicrobials and emphasise the urgent need for regulatory action and improved stewardship. This pilot study provides essential baseline data for developing farm-level national AMU surveillance system in Bangladesh.